Characterization of thermoplastic natural fibre composites made from woven hybrid yarn prepregs with different weave pattern. (September 2015) - Baghaei, Behnaz; Skrifvars, Mikael; Berglin, Lena
Abstract: This paper focuses on the effect of weave structure on mechanical behaviour and moisture absorption of the PLA/hemp woven fabric composites made by compression moulding. The unidirectional woven fabric prepregs were made from PLA (warp) and PLA/hemp wrapped-spun hybrid yarn (weft) with two different weave patterns; 8-harness satin and basket. Unidirectional composites with 30 mass% hemp content were fabricated from these prepregs, and compared to winded PLA/hemp hybrid yarn laminates with same composition. The composite from the satin fabric had significantly lowest porosities and best mechanical properties compared to the composite made from the winded hybrid yarn and basket fabric. The tensile, flexural, and impact strength were 88 MPa, 113.64 MPa, and 24.24 kJ/m 2, respectively. The effect of weave pattern on water absorption is significant. Although the composite from hybrid yarn laminate has larger water absorption than that of the pure PLA, it exhibits lower moisture absorption than both weaves.